Codelivery of thioridazine and doxorubicin using nanoparticles for effective breast cancer therapy - Jin X (Dove Medical Press, 2016)
Xun Jin,1,* Bingwen Zou,2,* Li Luo,1,* Chuanhong Zhong,3 Peilan Zhang,1 Hao Cheng,1 Yanfang Guo,1 Maling Gou1 1State Key Laboratory of Biotherapy and Cancer Center, West China Hospital, Sichuan University, and Collaborative Innovation Center for Biotherapy, 2Department of Thoracic Oncology, Cancer Center, West China Hospital, Medical School, Sichuan University, Chengdu, 3Department of Neurosurgery, The Affiliated Hospital of Luzhou Medical College, Luzhou, Sichuan Province, People’s Republic of China *These authors contributed equally to this work Abstract: Cancer chemotherapy can benefit from the combination of different anticancer drugs. Here, we prepared doxorubicin (Dox)- and thioridazine (Thio)-coloaded methoxy poly(ethylene glycol)-poly(L-lactic acid) (MPEG-PLA) nanoparticles (NPs) for breast cancer therapy. These NPs have an average particle size of 27 nm. The drug loading efficiencies of Thio and Dox are 4.71% and 1.98%, respectively. Compared to the treatment of Thio or Dox alone, the combination of Thio and Dox exhibited a synergistic effect in inhibiting the growth of 4T1 breast cancer cells in vitro. In addition, the Thio- and Dox-coloaded MPEG-PLA NPs could efficiently suppress the growth of breast cancer cells in vivo. This study suggests that Thio- and Dox-coloaded MPEG-PLA NPs might have potential applications in breast cancer treatment. Keywords: thioridazine, doxorubicin, codelivery, nanoparticles, breast cancer